Diversity of endophytic bacteria in different tissues of sengon (Falcataria moluccana) - MUSTIKA DEWI; NOOR RAHMAWATI; ALFI RUMIDATUL (Society for Indonesian Biodiversity, 2023)
Abstract. Dewi M, Rahmawati N, Rumidatul A. 2023. Diversity of endophytic bacteria in different tissues of sengon (Falcataria moluccana). Biodiversitas 24: 5747-5756. Endophytes are endosymbionts, usually bacteria or fungi, that live inside plants without causing disease. Endophytes are available in all plant species and play a role in enhancing plant resistance to insects, pathogens, and herbivores, increasing host growth, nutrient uptake, and increasing plant tolerance to abiotic stresses such as drought. The endophyte's ability to do all that is a result of the production of biological components or secondary metabolites, which may be the result of co-evolution or genetic transfer between endophytic microorganisms and host plants. In this study, the isolation, characterization and identification of endophytic bacteria from several different plant organs of sengon (Falcataria moluccana (Miq.) Barneby & J.W. Grimes) was carried out using the plant piece method in nutrient agar medium, and identification of selected isolates was carried out based on 16S rRNA. 16S rRNA sequencing results showed that 31 endophytic bacterial communities were successfully isolated from various parts of the sengon tree. Bacteria isolated from the stem were 3 strains, bark 7 strains, leaves 11 strains, and galls 10 strains. Molecular identification and phylogenetic analysis showed that the endophytes on the stem were Curtobacterium citreum and C. luteum, respectively. The endophytic bacteria on the bark are C. herbarum, C. luteum, C. pusillum, C. citreum and Azotobacter chroococcum. The endophytic bacteria on the leaves are A. chroococcum, C. citreum, C. herbarum and Lysinibacillus sphaericus. The endophytic bacteria in the gall are Enterobacter ludwigii, Kosakonia radicincitans, Citrobacter gizzii and Erwinia endophytica.